Osmotic dehydration of apricot: Kinetics and the effect of process parameters - Ispir, Ayse; Togrul, Inci Tuerk (Elsevier, 2009)
The effect of different parameters on the osmotic dehydration of apricot in terms of water loss and solid gain, such as the different osmotic matter the concentration of solution (40-70%, w/w), temperature (25-45 degrees C), the ratio of sample/solution (1/4-1/25), time, and geometry of sample were investigated. The increasing of temperature and concentration of osmotic medium caused increased water loss and solid gain. The decreasing of the ratio of sample to solution avoids significant dilution of the medium by water removal and subsequent decrease of osmotic driving force during the process. The water loss and solid gain was increased when the dimension of apricot was decreased. Effective diffusion and mass transfer coefficients of water as well as solid were estimated. The transport coefficients for water loss and solid gain (D-e and k) increases with an increase in osmotic solution concentration and increase in temperature. Non-linear analysis of the estimated D-e and k of water and solute reveal that these values depend on temperature and concentration of the osmotic solution as well as the combined effect of temperature and concentration. In addition, the effect of the ratio of sample to solution on these transport coefficients was modeled. The statistical comparison methods such as chi(2), MBE and RMSE were used to explore the confidence level of the models. (C) 2008 Published by Elsevier B.V. on behalf of The institution of Chemical Engineers.
Keywords: Apricot; Osmotic dehydration; Effective diffusivity; Mass transfer coefficient; Empirical models